Vibration responses analysis of an elastic-support cantilever beam with crack and offset boundary. (October 2017) - Zhang, Wensheng; Ma, Hui; Zeng, Jin; Wu, Shuang; Wen, Bangchun
Highlights: A finite element model of an elastic-support cantilever beam is developed. Combined effects of offset boundary and single-edge down-crack are analyzed. Combined effects of offset boundary and single-edge up-crack are analyzed. Stiffness asymmetry induced vibration responses are evaluated. Abstract: In this study, a finite element model of an elastic-support cantilever beam with crack and offset boundary is established by using mixed elements in ANSYS software. In the proposed model, different contact elements are adopted to describe the breathing effect of crack and offset boundary, and spring elements are used to simulate the elastic support, and the model is also validated by comparing the natural frequencies with those in published literatures. Based on the developed model, the combined effects of the crack and offset boundary on the system dynamic characteristics are studied. The results indicate that the amplitude of double frequency component (2 f e ) firstly decreases and then increases with the offset values when the crack position is on the opposite side of offset boundary. 2 f e may disappear when the crack and the offset boundary locate at a certain position. In addition, the more distant the offset boundary is, the more intense the system nonlinearity becomes. The amplitude of 2 f e increases with the offset values when the crack position is on the same side of offset boundary under a constant crack depth and location. Moreover, it also shows some complicated frequency components due to the gradually strengthened nonlinearity of the system with the increasing offset values, and the obvious distortion phenomenon in the phase plane portraits can be observed near the super-harmonic resonance region. This study can provide some basis for the diagnosis of beam-like structures with crack.